Book Review of Wexler & Sweet’s #MeToo-Informed Therapy: Counseling Approaches for Men, Women, and Couples - Pasyk, Victoria Summer (Canadian Journal of Counselling and Psychotherapy, 2022)
The #MeToo movement was an important cultural phenomenon that called on men to take accountability for their harmful behaviours, such as violating boundaries, engaging in sexual harassment, and committing sexual assaults. It was also an opportunity to validate survivors’ experiences and to unite men and women together as allies. However, #MeToo-type behaviours still occur today and many women are deeply affected by the harmful actions of men. This book was written as a clinical resource for counsellors working with men, women, and couples involved in or affected by #MeToo behaviours. This essential read covers the history of the #MeToo movement, explores gender norms, and suggests clinical strategies for intervention. By adding this book to their clinical library, counsellors will enrich their repertoire of skills for working with men who have offended, empowering female clients, and supporting couples affected by #MeToo behaviours.